PENEGAKAN HUKUM TINDAK PIDANA KEKERASAN MENGAKIBATKAN KEMATIAN YANG DILAKUKAN OLEH ANAK DI BAWAH UMUR (STUDI PUTUSAN PN SENGETI Nomor 1/Pid.Sus-Anak/2022/PN Snt) - Siagian, Artyssa Putri Siagian; Wetmen Sinaga; Lonna Yohanes Lengkong (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
There are more and more criminal acts committed by minors, one of which is violent crimes that result in death. This is what led the author to conduct research on several issues that can be raised regarding the reality of legal sanctions imposed on children and the application of criminal sanctions for child defendants in the judgments handed down by the Judge. The type of research used in this writing is normative juridical research with a statutory approach and a case approach, which is supported by data obtained from literature data including books, laws and regulations, and Court Decisions. The discussion in this Law Writing maps legal sanctions for violent criminal acts resulting in death committed by children from Law Number 1 of 2023 concerning the Criminal Code (KUHP) and Law Number 11 of 2012 concerning the Juvenile Criminal Justice System and Law Number 35 of 2014 concerning Child Protection which in practice have differences of opinion and have implications for punishment. Based on the results of the study that the application of sanctions to children perpetrators of violent crimes that result in death in the Sengeti District Court Decision Number: 1 / Pid.sus-Anak / 2022 / PN.Snt is to apply prison sanctions and job training to children.